The Effect of Corporate Governance on Financial Distress in Manufacturing Companies Listed on the Indonesia Stock Exchange 2016-2018 - B1034151014, Nuriah (Jurnal KIAFE, 2019)
The Effect of Corporate Governance on Financial Distress in Manufacturing Companies Listed on the Indonesia Stock Exchange 2016-2018. NuriahInternational Accounting ABSTRACT This study aims to examine the effect of corporate governance, namely the board of management, board of directors, independent commissioners and managerial ownership of the possibility of financial distress in manufacturing sector companies.This study uses secondary data obtained from annual reports and financial statements of manufacturing companies for the period of 2016 to 2018 which are listed on the Indonesia Stock Exchange. The sampling technique uses purposive sampling method which produces a sample of 126 companies. Data analysis methods used are descriptive statistical analysis and logistic regression analysis.The results of this study indicate that only the board of directors affect on financial distress while the board of management, independent commissioners and managerial ownership have no effect on financial distress. Another result is all variables simultaneously have no effect on financial distress. Keywords: financial distress, board of management, board of directors, independent commissioners, managerial ownership. REFERENCESAffifah, A. Dan Muslih, M. (2018). Pengaruh Leverage, Profitabilitas dan Good Corporate Governance Terhadap Financial Distress. Jurnal Ekonomi, Keuangan, Perbankan dan Akuntansi (EKSPANSI), 10 (2), 241-256. Altman, E, I. (1968). Financial Ratios, Discriminant Analysis and the Prediction of corporate Bankcruptcy. Jurnal of Finance, 589-609.Ananto, R. P, Mustika, R., dan Handayani, D. (2017). Pengaruh Good Corporate Governance (GCG), Leverage, Profitabilitas, dan Ukuran Perusahaan Terhadap Financial Distress pada Perusahaan Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia. Jurnal Ekonomi & Bisnis Dharma Andalas, 19 (1).Arief, M dan Pramuka, B,. A. 2007. Mekanisme Corporate Governance, Manajemen Laba Dan Kinerja Keuangan. Simposium Nasional Akuntansi X. Makassar.Bursa Efek Indonesia, Laporan Keuangan Tahunan 2016, 2017 dan 2018. (diakses di http://www.idx.co.id).Damayanti, L. D., Yuniarta, G, Y., dan Sinarwati, N., K. (2017). Analisis pengaruh Kinerja Keuangan, Komite Audit dan Kepemilikan Manajerial Terhadap Prediksi Financial Distress (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015). E-Journal S1 Ak Universitas Pendidikan Ganesha, 7 (1).Djumena, Erlangga (2018, 17 Oktober). Utang Rp 1 Triliun, Perusahaan Teh Sariwangi Dinyatakan Pailit. Dikutip 13 Agustus 2019 dari Kompas.com : https://ekonomi.kompas.com/read/2018/10/17/222200326/utang-rp-1-triliun-perusahaan-teh-sariwangi-dinyatakan-pailit?page=allFadhilah, F., N., dan Syafruddin, M. (2013). Analisis Pengaruh Karakteristik Corporate Governance Terhadap Kemungkinan Financial Distress. Diponegoro Journal of Accounting, 2 (2).Fathonah, A., N. (2016). Pengaruh Penerapan Good Corporate Governance Terhadap Financial Distress. Jurnal Ilmiah Akuntansi, 1 (2), 133-150.Ghozali, I. 2006. Aplikasi Analisis Multivariate dengan Program IBM SPSS. Semarang: Badan penerbit Universitas Diponegoro.Hanifah, O., E., dan Purwanto, Agus. (2013). Pengaruh Struktur Corporate Governance dan Financial Indicators Terhadap Kondisi Financial Distress. Diponegoro Journal of Accounting, 2 (2).Harahap, L, W. (2017). Pengaruh Mekanisme Corporate Governance dan Firm Size Terhadap Kondisi Financial Distress pada Perusahaan Property and Real Estate yang Terdaftar di BEI Tahun 2010-2014. Jurnal Riset Akuntansi & Bisnis, 17 (2).Hartanti, D., R., dan Hatane, E. (2017). Pengaruh Corporate Governance Terhadap Financial Distress pada Perusahaan Sektor Barang Konsumsi dan Perdagangan yang Terdaftar di Bursa Efek Indonesia. Business Accounting Review, 5 (2), 505-516Hendryadi & Suryani. 2015. Metode Riset Kuantitatif (Teori dan Aplikasi pada Penelitian Bidang Manajemen dan Ekonomi Islam). Jakarta: Kencana.IDX Factbook 2018. https://www.idx.co.id/media/4648/20181218_fb-2018.pdf (diakses 2 Juli 2019).Ikhsan, I., dan Suprasto, H. S. 2008. Teori Akuntansi dan Riset Multiparadigma. Yogyakarta: Graha Ilmu.Komite Nasional Kebijakan Governance. 2006. Pedoman Umum Good Corporate Governance IndonesiaMafiroh, A. Dan Triyono. (2016). Pengaruh Kinerja Keuangan dan Mekanisme Corporate Governance Terhadap Financial Distress. Riset Akuntansi dan Keuangan Indonesia, 1 (1).Ningrum, A., dan Hatane, S., E. (2017) Pengaruh Corporate Governance Terhadap Financial Distress. Business Accounting Review, 5 (1), 241-252.Raharjo, E. (2007). Teori Agensi dan Teori Stewarship dalam Perspektif Akuntansi. Fokus Ekonomi, 2 (1), 37-46.Sastriana, D., dan Fuad. (2013). Pengaruh Corporate Governance dan Firm Size Terhadap Perusahaan yang Mengalami Kesulitan Keuangan (Financial Distress). Diponegoro Journal of Accounting, 2 (3).Solihin, I. 2008. Corporate Social Responsibility from Charity to Sustainability. Bandung: Salemba EmpatSugiyono. 2003. Metode Penelitian Administrasi. Bandung: Alfabeta.Sugiyono, 2014. Metode Penelitian Bisnis (Pendekatan Kuantitatif, Kualitatif dan R&D). Bandung: Alfabeta.Sugiyono. 2014. Metode Penelitian Kombinasi (Mixed Methods). Bandung: Alfabeta.Tjager, I.N., et al. 2003. Corporate Governance : Tantangan dan Kesempatan bagi Komunitas Bisnis Indonesia, Serial Mastering Good Corporate Governance. Jakarta : Prenhanllindo.Toha, S. 2007. Penelitian Masalah Hukum Tentang Penerapan Good Corporate Governance pada Dunia Usaha. Jakarta: Badan Pembinaan Hukum Nasional.Wardhani, R. (2007). "Mekanisme Corporate Governance dalam Perusahaan yang Mengalami Permasalahan Keuangan. Jurnal Akuntansi dan Keuangan Indonesia, 4 (1), 95-114.